RANCANG BANGUN SISTEM MONITORING DAN PENGATURAN PADA SISTEM HOME REVERSE OSMOSIS DISPENSER BERBASIS INTERNET OF THINGS - Ricardo, Aldo; Abidin, Zainul; Zainuri, Akhmad (Jurnal Mahasiswa TEUB, 2024)
The availability of safe, clean water is a global priority, especially with the Sustainable Development Goals (SDGs) for 2030.However, data indicates that Indonesia still faces obstacles in meeting these goals, with most households experiencing limitedaccess to quality drinking water. This is an urgency because poor water quality can cause serious illnesses such as diarrhea which contributes to a high number of deaths each year, so assessing water quality is crucial, considering criteria such as pH, TDS, bacteria, and other physical factors. Therefore, monitoring and managing the Home Reverse Osmosis Dispenser system based on the Internet of Things (IoT) is an effective solution in monitoring water quality in real-time. The system monitors pH, TDS, temperature, and water level, with automatic controls to ensure water safety. Integration with UV water sterilizers aims to improve water quality by killing pathogenic microorganisms. Test results show the effectiveness of the system in generating accurate data, with low measurement differences between sensor readings and digital standardized comparison tools. The measurement accuracy rate for the pH sensor is 97.81%, for the TDS sensor is 96.76%, the temperature sensor is 98.9%, and the water level sensor 98.9%. The performance of each sensor produces the measurement value of each parameter very well. The addition of the water flow speed measurement feature and the calculation of the amount of water usage using the flow sensor also showed a high level of accuracy, namely 98.83% for measuring the speed of water flow and 97.69% for calculating the amount of water usage. Therefore, this system is expected to be an appropriate solution in increasing the availability of safe drinking water in urban areas in Indonesia in accordance with the SDGs. Keyword: Reverse Osmosis, drink water, Internet of Things